Analisa Citra Parasit Malaria Dalam Ruang Warna Hue Saturation Value (HSV) - Sulistyawati, Dwi Harini (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2018)
There are several types of images of malaria parasites, including purplish, greenish, yellowish and bluish. It is caused by giving a solution of geimsa on blood preparations. The color difference is inserted into the Hue Saturation Value (HSV) color space to get the conversion to 3 HSV color componenst, theHue (H) component, Saturation (S) component and Value (V) component.Of all types of color malaria parasites converted to the Hue Saturation Value (HSV) color space it is known that malaria parasites are most clearly seen in the Saturation (S) component and then the Value (V) component and the last inHue (H) somponent.The results of the three components are shown with a histogram to analyze the value trends. Keywords: malaria parasite, Hue Saturation Value (HSV) color space, histogram.